A Scoping Review on Conversational Memory and Characteristics of Conversations in Alzheimer's Disease. - Tanguay, Annick F. N.; Clough, Sharice; McCurdy, Ryan A.; Padilla, Victoria-Grace; Lord, Kaitlin M.; Brown-Schmidt, Sarah; Duff, Melissa C. (Journal of Speech, Language & Hearing Research, 2025)
Purpose: Typical late-onset Alzheimer's disease (AD) compromises episodic memory, the ability to encode new events and recollect past events. Much of the research on episodic memory in AD has relied on lab-based memory tasks (e.g., word lists, short stories). It is unclear how well these tasks characterize the impact of episodic memory impairments across different domains of everyday life, including conversational memory. The goal of the review was to establish what is known about conversational memory in AD, that is, memory for the content of conversations one overhears or in which one participates, such as utterances said and corresponding referents (e.g., "I remember discussing medical decisions with my children and I said [...] and they responded [...]"). Method: In this scoping review, we followed the JBI Manual for Evidence Synthesis and PRISMA Extension for Scoping Reviews guidelines to conduct the scoping review. We retained 121 reports on conversation and three reports on conversational memory out of the 8,351 unique records found on PubMed, CINAHL, PsycINFO, Web of Science, Cochrane, and Embase and in relevant reviews. Included reports had to involve conversation in any format and on any topic, include an AD population, be peer-reviewed, be in English, and be published between 1990 and 2022. Results: None of the studies investigated memory for spontaneous conversation. Although most studies on conversation did report on key characteristics of the interactional context (e.g., level of structure, number and category of conversational partners), studies also left several important details unspecified, such as hearing/vision (omitted in 67% studies) and diagnostic process (omitted in 33% studies). Studies described a broad range of behaviors during conversation, with most concerning verbal behaviors (e.g., repetitions, disfluency, ambiguity) and only 29% nonverbal behaviors (e.g., facial expression, head and hand gestures, eye gaze). Given the rarity of studies on conversational memory, we primarily summarized existing knowledge about conversation and methodological considerations to inspire hypotheses for future research on conversational memory in AD and to illuminate decisions regarding study design. Conclusions: This review revealed a wide gap in knowledge on conversational memory in AD and offers a path to accelerating research on the topic. Conversational memory may be an important factor in promoting independence, participation in health care, and social well-being. Supplemental Material: https://doi.org/10.23641/asha.30535784